The common touch. Popular literature from the Elizabethans to the restoration - Scanlon, Paul A.; Roscoe, Adrian (Cambridge Scholars Publishing, 2014)
During the Elizabethan Age and for the following hundred and fifty years, such figures as Shakespeare and Jonson, Milton and Pope dominated the English literary scene. But what was the vast majority of society really watching, reading and singing? This pioneering anthology, set in two volumes, attempts to answer this question by offering a wide selection of material, ranging from broadside ballads and drolls to witch trial reports and political newsbooks.